(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
The defence plan, as a summary of the planning documents is brought in order to designate the condition in which the subjects will act in a specific and concrete security situation, and respectively, to include as much precise conditions that will occur during the realization of the planned goals. The defence plan, expressed through making more variances, constitutes the basic mechanism that the state headsmen should conduct in case of warfare. Likewise, the defence plan should be focused on well defined goals and should be based on concrete and real conditions so it can connect the level of credibility of its sources, with the need for defined plans.